1956
DOI: 10.4319/lo.1956.1.1.0061
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in the Ocean as a Function of Light Intensity1

Abstract: Photosynthesis was measured in 14 species of marine plankton algae in relation to light intensites within the entire range to which natural phytoplankton populations may be exposed. A mean curve was constructed showing relative photosynthesis in marine phytoplankton as related to light intensity. From this curve and surface radiation data, relative values for photosynthesis were determined throughout the day at the surface and at depths in the ocean at which the surface intensity is reduced by given amounts. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
16

Year Published

1975
1975
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(177 citation statements)
references
References 11 publications
8
153
0
16
Order By: Relevance
“…Observations show that the primary production reduces rapidly to 20 % or less of the surface value below a threshold of 10 W m −2 (Parsons et al, 1984;Ryther, 1956;Sarmiento and Gruber, 2006). Moreover higher ocean temperatures (those in the tropics) enhance the respiration rates, resulting in high compensation irradiance (Ryther, 1956;Parsons et al, 1984;Lopez-Urrutia et al, 2006;Regaudix-de-Gioux and Duarte, 2010). A study by Regaudix-de-Gioux and Duarte (2010) reported the mean value of compensation irradiance over the Arabian Sea as 0.4 ± 0.2 mol photon m −2 day −1 , which is close to 10 W m −2 day −1 .…”
Section: Community Compensation Depth (Zc) Parameterisationmentioning
confidence: 99%
“…Observations show that the primary production reduces rapidly to 20 % or less of the surface value below a threshold of 10 W m −2 (Parsons et al, 1984;Ryther, 1956;Sarmiento and Gruber, 2006). Moreover higher ocean temperatures (those in the tropics) enhance the respiration rates, resulting in high compensation irradiance (Ryther, 1956;Parsons et al, 1984;Lopez-Urrutia et al, 2006;Regaudix-de-Gioux and Duarte, 2010). A study by Regaudix-de-Gioux and Duarte (2010) reported the mean value of compensation irradiance over the Arabian Sea as 0.4 ± 0.2 mol photon m −2 day −1 , which is close to 10 W m −2 day −1 .…”
Section: Community Compensation Depth (Zc) Parameterisationmentioning
confidence: 99%
“…This can be interpreted as a light limitation of the production rate (e.g. Ryther, 1956;Kirk, 1994). Cloud coverage can affect rates of production by a factor of up to 4.5 (Riegman and Colijn, 1991).…”
Section: Production and Respiration Ratesmentioning
confidence: 99%
“…Because chlorophyll ~· roughly approximates the rate of photosynthesis, it has been used as a measure of productivity (Ryther 1956, Waters 1961, Yount 1956. Several studies have shown a strong positive correlation between chlorophyll content and biomass (McConnell andSigl,er 1959, Grzenda andBrehmer 1960).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%